SOME REMARKS ON THE DOCUMENTS ON THE HISTORY OF THE KHANATE OF KHIVA - Tulibayeva Zhuldyz; Allaeva Nigora; Ustagaliyev Ernar (Scientific Journal of Pedagogy and Economics, 2019)
The article considers the archival documents containing information on the history of the Khanate of Khiva. The extant Khivan documents in their content and variety of factual material occupy an important place among the written sources of the Central Asian region. The materials of the fund “The Chancellery of Khivan Khan” were officially recognized by the Government of Uzbekistan as highly valuable. The authors of the article concluded that the Khivan archival documents are reliable sources for studying the history of the Qazaqs who lived in the territory of the Khanate. The documents, which contain data allowing the reconstruction of the foreign policy relations of the Khivan Khans with neighbouring states, including Qazaq zhuzes, have been preserved. The article was prepared within the framework of the grant of the Ministry of Education and Science of the Republic of Kazakhstan that finance the fundamental and applied research.